The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s41959-020-00034-4
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial educators: vital enablers to support the education sector to reimagine and respond to the challenges of COVID-19

Abstract: This article examines the experiences of the educator as a key actor in entrepreneurship education. Since the 1990s, the education sector has been called upon to create more 'entrepreneurs' to find solutions to global problems leading to entrepreneurship education. The educator is a key participant in the process of entrepreneurship education, but too little is known or understood about their experiences. Employing an interpretative phenomenological approach with ten UK-based higher education entrepreneurship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
(75 reference statements)
1
5
0
2
Order By: Relevance
“…The findings from the current study highlight how, for our small sample of expatriate entrepreneurs in the UAE, identifying as resilient and having a network of support were vital in navigating the pandemic. This is in line with emerging research and supports several calls to reimagine, or reset, entrepreneurial education (e.g., Langston, 2020; Ratten & Jones, 2021). For example, higher education and government support programs can integrate a focus on resilience when working with budding entrepreneurs (Chadwick & Raver, 2020; Ratten & Jones, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…The findings from the current study highlight how, for our small sample of expatriate entrepreneurs in the UAE, identifying as resilient and having a network of support were vital in navigating the pandemic. This is in line with emerging research and supports several calls to reimagine, or reset, entrepreneurial education (e.g., Langston, 2020; Ratten & Jones, 2021). For example, higher education and government support programs can integrate a focus on resilience when working with budding entrepreneurs (Chadwick & Raver, 2020; Ratten & Jones, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Berg (2004), stated that the elements of content analysis that can be considered, such as terms, semantic, characters, concepts, themes, items, and paragraphs. (Langston, 2020). Individuals must possess some criteria to be categorized as ideal and competent entrepreneurship educators.…”
Section: Regardingmentioning
confidence: 99%
“…Entrepreneurship education is one of the critical forces for the economy and education system of any country, and hence, many institutions including B-Schools began offering entrepreneurship as an elective course (Basu, 2014). Langston (2020) found that it is necessary to review and change the education system in the post-COVID-19 situation. The entrepreneurial educators can help to reimagine program contents, delivery structure, research and innovation and support transformative action.…”
Section: Covid-19 and Higher Educational Institutes: Challenges And A...mentioning
confidence: 99%